Mesospheric Bore Evolution and Instability Dynamics Observed in PMC Turbo Imaging and Rayleigh Lidar Profiling Over Northeastern Canada on 13 July 2018. Issue 14 (13th July 2020) - Fritts, David C.; Kaifler, Natalie; Kaifler, Bernd; Geach, Christopher; Kjellstrand, C. Bjorn; Williams, Bifford P.; Eckermann, Stephen D.; Miller, Amber D.; Rapp, Markus; Jones, Glenn; Limon, Michele; Reimuller, Jason; et al.
Abstract: Two successive mesospheric bores were observed over northeastern Canada on 13 July 2018 in high‐resolution imaging and Rayleigh lidar profiling of polar mesospheric clouds (PMCs) performed aboard the PMC Turbo long‐duration balloon experiment. Four wide field‐of‐view cameras spanning an area of 75 × 150 km at PMC altitudes captured the two evolutions occurring over 2 hr and resolved bore and associated instability features as small as 100 m. The Rayleigh lidar provided PMC backscatter profiling that revealed vertical displacements, evolving brightness distributions, evidence of instability character and depths, and insights into bore formation, ducting, and dissipation. Both bores exhibited variable structure along their phases, suggesting variable gravity wave (GW) source and bore propagation conditions. Both bores also exhibited small‐scale instability dynamics at their leading and trailing edges. Those at the leading edges comprised apparent Kelvin‐Helmholtz instabilities that were advected downward and rearward beneath the bore descending phases extending into an apparently intensified shear layer. Instabilities at the trailing edges exhibited alignments approximately orthogonal to the bore phases that resembled those seen to accompany GW breaking or intrusions arising in high‐resolution modeling of GW instability dynamics. Collectively, PMC Turbo bore imaging and lidar profiling enabled enhanced definition of bore dynamics relative to what has been possible by previous ground‐based observations, and a potential to guide new, three‐dimensional modeling of bore dynamics. The observed bore evolutions suggest potentially important roles for bores in the deposition of energy and momentum transported into the mesosphere and to higher altitudes by high‐frequency GWs achieving large amplitudes. Key Points: Mesospheric bores are dramatic events that dominate local instability dynamics accompanying their passage Mesospheric bores can exhibit significant variability in their evolution in time and along their phases Mesospheric bores can exhibit significant instability dynamics at smaller spatial scales at their leading and trailing edges